Tumors of the lateral ventricles: a clinico-pathological study - Ojha, Sandeep; Fernandes, Gwendolyn; Shenoy, Asha (International Journal of Medical Research and Review, 2015)
Introduction: Brain tumors are rare compared to other fatal and life-diminishing diseases and its incidence is increasing. The objective is to study the lateral ventricular tumors with reference to age groups, gender, anatomical location, the histopathological features including the histological grades, and the clinico- radio- pathological correlation of the above cases. Methodology: Retrospective analysis of tumors of the lateral ventricle of the CNS diagnosed in the department of Neuropathology at a tertiary care and referral hospital, from January 2001 to June 2009. Results: Average Incidence of primary lateral ventricular tumor was 1.6%, that tumor involve the left lateral ventricle (46.3%) more commonly than the right lateral ventricle (29.9%). Commonest tumors in our study were the Neuronal and mixed glioneuronal tumors [31%]. 78.1% of the lateral ventricular tumors were correctly diagnosed on radiology. Conclusion: Commonest tumors were Neuronal and mixed glioneuronal tumors. Most of the tumors belonged to low WHO grade. Fairly good correlation was found between radiological and histopathological diagnosis.